Helping Mothers Survive, Bleeding After Birth: An Evaluation of Simulation-based training in a Tertiary Hospital of Eastern Nepal: - KC, Heera; Dhakal, Sabina; Khatri, Usha; Upadhyaye, Shweta; Sharma, Ismita; Dhungana, Animesh; Dhungana, Ranjan (Birat Journal of Health Sciences, 2025)
Introduction: Postpartum hemorrhage is the leading cause of maternal mortality worldwide, especially in resource-limited settings like Nepal. Simulation-based training is a proven educational approach that equips healthcare providers with the critical knowledge and skills necessary to manage postpartum hemorrhage effectively. Objectives: The objective was to evaluate the effectiveness of simulation-based training on Helping Mothers Survive: Bleeding After Birth in strengthening healthcare providers’ competencies in managing PPH and shock in a tertiary hospital in eastern Nepal. Methodology: A simulation-based educational intervention was conducted in two phases: first phase took place on 26-27th June, 2023 and the second on 3-4th January, 2024, among 44 healthcare professionals. Helping Mothers Survive standardized assessment tools were used for Pre-test and Post-test knowledge on postpartum hemorrhage, and shock management and skill evaluations in Active Management of Third Stage of Labour, atony, bimanual compression, and condom tamponade, and shock management. Data were analyzed using paired t-tests in SPSS version 23, with p < 0.05 considered significant. Results: Among 44 healthcare professionals the mean knowledge scores for postpartum hemorrhage and shock management improved significantly from 11.77 ± 1.89 to 14.0 ± 1.01 (p < 0.001) and 4.27 ± 1.32 to 7.38 ± 0.56 (p < 0.001) respectively. OSCE results showed that all participants passed Active Management of Third Stage of Labour L and shock management. Forty-two out of 44 participants (95.45%) successfully performed atony management, bimanual compression, and condom tamponade. Conclusion: Simulation-based education significantly improved knowledge and skills among healthcare professionals working in maternity units. However, two participants who fell short highlight the need for frequent, ongoing training.